Evaluation of the Tibial Nerve with Shear-Wave Elastography: A Potential Sonographic Method for the Diagnosis of Diabetic Peripheral Neuropathy - Dikici, Atilla Suleyman; Ustabasioglu, Fethi Emre; Delil, Sakir; Nalbantoglu, Mecbure; Korkmaz, Bektas; Bakan, Selim; Kula, Osman; Uzun, Nurten; Mihmanli, Ismail; Kantarci, Fatih (Radiology, 2017)
Purpose To evaluate the value of shear-wave elastography (SWE) in the detection of diabetic peripheral neuropathy (DPN) of the tibial nerve. Materials and Methods This study was approved by the institutional review board, and written informed consent was obtained from all study participants. The study included 20 diabetic patients with DPN (10 men, 10 women), 20 diabetic patients without DPN (eight men, 12 women), and 20 healthy control subjects (nine men, 11 women). The tibial nerve was examined at 4 cm proximal to the medial malleolus with gray-scale ultrasonography and SWE. The nerve cross-sectional area (in square centimeters) and the mean nerve stiffness (in kilopascals) within the range of the image were recorded. Inter- and intrareader variability, differences among groups, and correlation of clinical and electrophysiologic evaluation were assessed with intraclass correlation coefficients, the Mann Whitney U test, and the Wilcoxon signed rank test. Results Between diabetic patients with and diabetic patients without DPN, mean age (60 years [range, 38-79 years] vs 61 years [range, 46-75 years], respectively), mean duration of diabetes (10 years [range, 1-25 years] vs 10 years [range, 2-26 years]), and mean body mass index (31.4 kg/m [range, 24.7-48.1 kg/m ] vs 29.8 kg/m [range, 22.9-44.0 kg/m ]) were not significantly different. Diabetic patients without DPN had significantly higher stiffness values on the right side compared with control subjects (P < .001). Patients with DPN had much higher stiffness values on both sides compared with both diabetic patients without DPN (P < .001) and healthy control subjects (P < .001). A cutoff value of 51.0 kPa at 4 cm proximal to the medial malleolus revealed a sensitivity of 90% (95% confidence interval [CI]: 75.4%, 96.7%) and a specificity of 85.0% (95% CI: 74.9%, 91.7%). Conclusion Tibial nerve stiffness measurements appear to be highly specific in the diagnosis of established DPN. The increased stiffness in subjects without DPN might indicate that the nerve is affected by diabetes. RSNA, 2016 Online supplemental material is available for this article.